2021
DOI: 10.1039/d0cp06497a
|View full text |Cite
|
Sign up to set email alerts
|

The defect chemistry of non-stoichiometric PuO2±x

Abstract: An increased knowledge of the chemistry of PuO2 is imperative for the design of procedures to store, dispose, or make use of PuO2. In this work, point defect concentrations in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 80 publications
3
23
0
Order By: Relevance
“…The CRG potential is a many-body potential model used to describe actinide oxide systems that achieves good reproduction of thermodynamic and mechanical properties. Previous work demonstrated that the phonon DOS for PuO 2 produced using the CRG potential compares reasonably well to the experimental data of Manley et al 2 , 45 The calculation of vibrational entropies, S vib , closely follows the approach described in refs ( 40 , 46 , 47 ), where using eq 1 , defect entropies are calculated from the normal vibrational frequencies, v n , which are themselves calculated by diagonalizing the dynamical matrix of the system In this formula, h is Planck’s constant, N is the number of atoms in the crystal, T is the temperature, and k B is the Boltzmann constant. In this study, the system to calculate vibrational entropies is a 4 × 4 × 4 expansion of the PuO 2 unit cell.…”
Section: Methodssupporting
confidence: 75%
See 4 more Smart Citations
“…The CRG potential is a many-body potential model used to describe actinide oxide systems that achieves good reproduction of thermodynamic and mechanical properties. Previous work demonstrated that the phonon DOS for PuO 2 produced using the CRG potential compares reasonably well to the experimental data of Manley et al 2 , 45 The calculation of vibrational entropies, S vib , closely follows the approach described in refs ( 40 , 46 , 47 ), where using eq 1 , defect entropies are calculated from the normal vibrational frequencies, v n , which are themselves calculated by diagonalizing the dynamical matrix of the system In this formula, h is Planck’s constant, N is the number of atoms in the crystal, T is the temperature, and k B is the Boltzmann constant. In this study, the system to calculate vibrational entropies is a 4 × 4 × 4 expansion of the PuO 2 unit cell.…”
Section: Methodssupporting
confidence: 75%
“… 15 The decision and justification for the selection of our U and J parameters are discussed in detail in our previous work, which also reports the equilibrium properties the HSE06 and PBEsol + U ( U = 7.0 eV) functionals attain simulating PuO 2 . 2 In summary, it was chosen to reproduce the HSE06 band gap to set U as the experimental data shows a large variation, and this functional has been proven to replicate experimental band gaps. 37 In the Supporting Information , we present a comparison of the projected densities of states (DOS) obtained using the PBEsol + U and HSE06 functionals as well as evidence that while the choice of U impacts the DOS, the impact to the DFT formation energy of a defect is minimal.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations